ADOPSI DEVSECOPS UNTUK MENDUKUNG METODE AGILE MENGGUNAKAN TRIVY SEBAGAI SECURITY SCANNER DOCKER IMAGE DAN DOCKERFILE - Evangs Mailoa; Panca Rizki Perkasa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Compliance with personal data protection laws requires electronic system operators to pay more attention to security in applications. Security testing which is usually done at the end of the SDLC makes Agile principles incompatible with advantages that prioritize acceleration, adaptability and responsiveness to change. DevSecOps implementation using Trivy will insert a security scanner process for applications that are deployed in containerized form. The continuous process of security scanning integrated in CI/CD will increase the awareness of developers in terms of application security, so that developers will more quickly fix these problems and avoid security problems at the end of the SDLC.